ANALISIS LAPORAN KEUANGAN DITINJAU DARI CURRENT RATIO, CASH RATIO, DEBT TO ASSET RATIO DAN DEBT TO EQUITY RATIO DI KOPERASI SIMPAN PINJAM “RIAS” P1 MARDIHARJO KABUPATEN MUSI RAWAS - Nasruddin Nasruddin; Yulfa Rabeta; Eka Apriana (Jurnal Media Ekonomi (JURMEK), 2018)
This study aims to analyze the financial statements in terms of the current ratio, cash ratio, debt to asset ratio and debt to equity ratio in the savings and loan cooperatives “RIAS” P1 Mardiharjo district of MusiRawas for six years from 2012 – 2017. The method used is qualitative methods. From the results of the analysis it can be explained that for (1) the calculation of the current ratio (CR) in the savings and load cooperatives “RIAS’ in 2012 CR amounted to 145%, then in can be criticized GOOD LESS, in 2013 CR amounted 144% included in the GOOD LESS, in 2014 CR amounted to 151% included in GOOD ENOUGH criteria, know 2015 CR amounted to 136 included in GOOD LESS criteria, in 2016 CR amounted to 130% included in GOOD LESS criteria, in 2017 CR amounted to 134% included in GOOD LESS criteria.(2) cash ratio calculation in 2012 was 10% it can be criticized GOODENOUGH, 2013 cash ratio of 26% included in GOOD criteria, 2014 cash ratio of 23% included in GOOD criteria, 2015 cash ratio of 39% included in the VERY GOOD criteria, the 2016 cash ratio of 39% included in the VERY GOOD criteria, 2017 cash ratio of 34% included in GOOD criteria. (3) the calculation of debt to asset ratio (DAR) in 2012 amounted to 60% it can be criticized GOOD ENOUGH, in 2013 DAR amounted to 62% included in the GOOD LESS criteria, in 2014 DAR amounted to 51% included in GOOD ENOUGH criteria, in 2015 DAR amounted to 66% included in the GOOD LESS criteria, in 2016 DAR amounted to 69% included in the GOOD LESScritera, in 2017 DAR amounted to 71% included in the GOOD LESS criteria. (4) debt to equity ratio (DER) calculation in 2012 amounted to 155% it can be criticized GOOD LESS, in 2013 DER amounted to167% included in the GOOD LESS criteria, in 2014 DER amounted to 105% includedinGOOD ENOUGH criteria, in 2015 DER amounted to 201% included in the NOT GOOD criteria, in 2016 DER amounted to 224% included in the NOT GOOD criteria, in 2017 DER amounted to 245% included in the NOT GOOD .